39 Staying Out of Trouble: Strategies Based on Recent OMIC Oculofacial Plastic Surgery Claims (Ophthalmic Plastic Surgery of the Upper Face, 2020)
Every treatment or surgery has the risk of failing to accomplish the intended objective of improving patients’ condition or appearance. Hence, every physician must learn to manage this disappointing outcome and help patients move forward with acceptance or additional treatment. Breakdown in the physician–patient relationship can contribute to the likelihood of medical malpractice claims against the physician. This chapter discusses the causes for common problems and suggests strategies to avoid malpractice claims.
Keywords: malpractice; liability; claim; indemnity; informed consent; standard of care; plaintiff; defendant; negligence